Identifying the Association Between Older Adults' Characteristics and Their Health-Related Outcomes in a Transition Care Setting: A Retrospective Audit - Jo-Aine Hang; Jacqueline Francis-Coad; Chiara Naseri; Angela Jacques; Nicholas Waldron; Kate Purslowe; Anne-Marie Hill (Frontiers Media S.A., 2021)
Introduction: Continued evaluation of Transition Care Programs (TCP) is essential to improving older adults' outcomes and can guide which older adults may benefit from undertaking TCP. The aim of this study was to audit a transition care service to identify the association between the characteristics of older adults undertaking a facility-based TCP and (i) discharge destination and (ii) functional improvement.Materials and methods: An audit (n = 169) of older adults aged 60 years and above who completed a facility-based TCP in Australia was conducted. Outcomes audited were performance of activities of daily living (ADL) measured using the Modified Barthel Index (MBI) and discharge destination. Data were analyzed using logistic regression and linear mixed modeling.Results: Older adults [mean age 84.2 (±8.3) years] had a median TCP stay of 38 days. Fifty-four older adults (32.0%) were discharged home, 20 (11.8%) were readmitted to hospital and 93 (55%) were admitted to permanent residential aged care. Having no cognitive impairment [OR = 0.41 (95% CI 0.18-0.93)], being independent with ADL at admission [OR = 0.41 (95% CI 0.16-1.00)] and a pre-planned team goal of home discharge [OR = 24.98 (95% CI 5.47-114.15)] was significantly associated with discharge home. Cases discharged home showed greater improvement in functional ability [MBI 21.3 points (95% CI 17.0-25.6)] compared to cases discharged to other destinations [MBI 9.6 points (95% CI 6.5-12.7)].Conclusion: Auditing a facility-based TCP identified that older adults who were independent in ADL and had good cognitive levels were more likely to be discharged home. Older adults with cognitive impairment also made clinically significant functional improvements.